Influência do treinamento em esteira sobre a atividade de neurônios vasopressinérgicos e ocitocinérgicos em ratos hipertensos - Henrique Pereira Santiago (2017)
Aim: To asses the influence of physical training on neuronal activation and on hypothalamic expression of vasopressin and oxytocin in SHR rats after graded running until fatigue, and whether such interference is followed by modifications on heat balance and exercise performance. Material and methods: Wistar non-hypertensive (systolic pressure 104 ± 2,7 mmHg) and SHR (systolic pressure 170 ± 2,6 mmHg) rats, aged 3-4 weeks were divided into: (1) trained Wistar group; (2) untrained Wistar group; (3) Naïf Wistar group; (4) trained SHR group; (5) untrained SHR group; (6) Naïf SHR group. The physical training protocol consisted of running during 8 weeks, 5 days a week. The exercise intensity and duration were gradually increased until the animals reached the velocity of 25 m/min during 60 minutes. After the physical training period, both trained and untrained Wistar and SHR animals were submitted to a session of graded exercise until fatigue (starting at 10 m/min, 1 m/min increment every 3 min until fatigue, 5% inclination of the treadmill). While the animals performed such graded exercise protocol, body and tail temperatures, as well as total time of exercise until fatigue were registered. Workload, body heating rate, heat storage rate and body temperature threshold for tail vasodilation were determined from the data obtained. Ninety minutes after finishing the graded exercise session, the animal’s brains were removed and prepared for immunohistochemistry analysis. Fos immunomarcation was carried out in the following hypothalamic areas: median preoptic nucleus (MnPO), medial preoptic nucleus (MPO), paraventricular nucleus of the hypothalamus (PVN) and supraoptic nucleus (SON). Results: as expected, trained non-hypertensive and hypertensive animals had increased time of exercise until fatigue in comparison with the corrresponding untrained rats (Wistar: 73.2 ± 3.5 min, trained vs 39.2 ± 2.1 min, untrained; SHR: 41.3 ± 2.0 min, trained vs 25.7 ± 0.6 min, untrained, p < 0.01), as well as higher workload performed (p < 0.01). SHR trained anduntrained rats showed enhanced body temperature than trained and untrained Wistar rats from 12 and 6 minutes of exercise, respectively. In regard to the tail, SHR animals demonstrated similar temperature to Wistar animals. Body temperature threshold for tail vasodilation was also equal between SHR and Wistar animals. Both trained and untrained SHR rats showed heat imbalance characterized by an increase of 300% and 266%, respectively, in body heating rate, and by an increase of 304% and 216%, respectively, in heat storage rate in comparison with the corresponding Wistar rats. Physical training enhanced c-Fos immunomarcation in the MnPO, the MPO and the PVN of Wistar and SHR rats compared with untrained animals, being this response reduced in SHR rats (p < 0.01). Nevertheless, physical training did not affect c-fos expression in the SON of SHR and Wistar rats. Vasopressin and ocytocin immunomarcation within the PVN, co-localized or not with c-fos, were higher in trained than untrained animals (p < 0.01), being the response lower in SHR rats (p < 0.01). Physical training did not alter the density of vasopressinergic neither ocytocinergic neurons within the SON (p < 0.01). However, the expression of vasopressin and ocytocin in the SON of trained and untrained SHR rats was significantly lower in comparison with its corresponsing Wistar controls (p < 0.01). Neuronal activation of the MnPO, the MPO, the PVN and the SON was associated with the workload performed by the animals during graded running until fatigue (Wistar: MnPO, r = 0,94; MPO, r = 0,96; PVN, r = 0,92; SON, r = 0,77; p < 0,01; SHR: MnPO, r = 0,92; MPO, r = 0,95; PVN, r = 0,93; SON, r = 0,91; p < 0,01). Conclusions: the data indicate that physical training potenciates neuronal activity within the MnPO, the MPO and the PVN of Wistar and SHR rats submitted to grade exercise unti fatigue, which is related with improved exercise performance. Moreover, physical training increases the activity of vasopressinergic and ocytocinergic neurons in the PVN of non-hipertensyve and hypertensive animals, being such neural recruitment associated with the enhanced exercise performance.Nevertheless, such hypothalamic responses are atenuated in SHR rats indicanting an inhibitory effect of arterial hypertension on neronal plasticity induced by exercise.